2013
DOI: 10.5582/ddt.2013.v7.6.212
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine and related active compounds: A review of their role on hepatitis B virus infection

Abstract: Since the significant public health hazard of Hepatitis B virus (HBV) infection and obvious drug resistance and dose-dependent side effects for common antiviral agents (e.g., interferon α, lamivudine, and adefovir), continuous development of agents to treat HBV infection is urgently needed. Traditional Chinese medicine (TCM) is an established segment of the health care system in China. Currently, it is widely used for chronic hepatitis B (CHB) in China and many parts of the world. Over a long period of time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 56 publications
0
73
0
Order By: Relevance
“…Wogonin (5,) is a flavonoid compound extracted from the roots of Scutellaria baicalensis. Wogonin has been shown to have suppressant effects on the replication of vesicular stomatitis virus (VSV) (Blach-Olszewska et al, 2008), hepatitis B virus (HBV) (Guo et al, 2007;Huang et al, 2000;Qi et al, 2013), and human papilloma virus (HPV) (Kim et al, 2013). Currently, limited number of studies suggests the antiviral effects of plant-derived compounds against Varicellazoster virus (VZV) infection.…”
Section: Introductionmentioning
confidence: 98%
“…Wogonin (5,) is a flavonoid compound extracted from the roots of Scutellaria baicalensis. Wogonin has been shown to have suppressant effects on the replication of vesicular stomatitis virus (VSV) (Blach-Olszewska et al, 2008), hepatitis B virus (HBV) (Guo et al, 2007;Huang et al, 2000;Qi et al, 2013), and human papilloma virus (HPV) (Kim et al, 2013). Currently, limited number of studies suggests the antiviral effects of plant-derived compounds against Varicellazoster virus (VZV) infection.…”
Section: Introductionmentioning
confidence: 98%
“…Notably, despite high efficacies, most of the HBVpol inhibitors, such as lamivudine, adepovir, entecavir, and so forth lead to the emergence of drug‐resistance and failure to chemotherapy (Teo & Locarnini, ). In the recent decade, traditional and indigenous herbal medicines or plant metabolites have gained much attention for their remarkable anti‐HBV effects (Arbab, Parvez, Al‐Dosari, et al, ; Arbab, Parvez, Al‐Dosari, & Al‐Rehaily, ; Chen & Zhu, ; Parvez et al, ; Parvez, Arab, Al‐Dosari, & Al‐Rehaily, ; Qi et al, ; Wang, Zhang, & Bonkovsky, ; Wu, ; Yang et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…ex Balf, commonly known as ‘rhubarb’, has long been widely used in traditional Chinese herb, and also as Chinese dishes, and rhubarb has been officially listed in the pharmacopoeias of China, Japan, and Europe . A series of studies has shown that rhubarb can be used to treat ischemic stroke, and has anti‐inflammatory, anti‐cancer and anti‐hepatitis B virus (HBV) effects, among others. The main compounds in rhubarb include rhein, emodin, aloe‐emodin, physcion, chrysophanol, sennoside A, sennoside B, gallic acid, and catechin .…”
Section: Introductionmentioning
confidence: 99%